High-Power Lasers - Vladimir Chvykov (Encyclopedia)
High-power lasers play an important role in modern science, industry, and medicine. A significant milestone was reached on 5 December 2022, when Inertial Confinement Nuclear Fusion (ICF) achieved scientific breakeven, releasing more energy than the input laser energy. Additionally, Extreme Ultraviolet Lithography (EUVL) has enabled the development of microchips with 3 nm process nodes, marking a leap in semiconductor technology. These examples, together with the recent achievement of 10 PW (1015 W) laser output, herald remarkable advancements in technology and science. Laser systems are broadly classified based on their operating regimes into two main categories: Continuous Wave (CW) operation, where the laser is continuously pumped and emits a steady beam of light, and the pulsed regime, in which the laser produces single or multiple pulses at various repetition rates. This review will primarily focus on pulsed laser systems, exploring their various types and recent technological advancements.